The value of manure - Manure as co-product in life cycle assessment - Leip, Adrian; Ledgard, Stewart; Uwizeye, Aimable; Palhares, Julio C.P.; Fernanda Aller, M.; Amon, Barbara; Binder, Michael; Cordovil, Claudia M.d.S.; De Camillis, Camillo; Dong, Hongming; Fusi, Alessandra; Helin, Janne; et al. (Elsevier, 2019)
Livestock production is important for food security, nutrition, and landscape maintenance, but it is associated with several environmental impacts. To assess the risk and benefits arising from livestock production, transparent and robust indicators are required, such as those offered by life cycle assessment. A central question in such approaches is how environmental burden is allocated to livestock products and to manure that is re-used for agricultural production. To incentivize sustainable use of manure, it should be considered as a co-product as long as it is not disposed of, or wasted, or applied in excess of crop nutrient needs, in which case it should be treated as a waste. This paper proposes a theoretical approach to define nutrient requirements based on nutrient response curves to economic and physical optima and a pragmatic approach based on crop nutrient yield adjusted for nutrient losses to atmosphere and water. Allocation of environmental burden to manure and other livestock products is then based on the nutrient value from manure for crop production using the price of fertilizer nutrients. We illustrate and discuss the proposed method with two case studies.
Keywords: Life cycle assessment; Livestock supply chains; Nutrients; Fertilizer; Allocation; Manure